Method for reinforcing agricultural waste fermentation by carbon-based material to produce growth-promoting and stress-resistant fertilizer
Patent Information
- Application Number
- CN202611070258.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]本发明提供了一种炭基材料强化农业废弃物发酵制促生抗逆肥料的方法,解决了养分易流失、炭基材料与农业废弃物发酵物多为简单混合添加,未对炭基材料进行改性活化,导致炭基材料的增效优势无法发挥,制备的肥料促生、抗逆性能有限的问题
[0028] (1) In the technical solution of the present invention, the pyrolysis and carbonization of livestock waste and acidification form activated carbon-based materials. On the one hand, the activated carbon-based materials have a high porosity structure, which serves as adsorption sites for chelated trace elements. The chelated trace elements are loaded onto the activated carbon-based materials, avoiding the direct addition of chelated trace elements to fertilizers, which are prone to migration and precipitation, affecting the growth-promoting and stress-resistant effects of fertilizers. On the other hand, the carbon-based materials are acidified to remove inorganic ash and heavy metal impurities inside the biochar, clear the microporous structure, increase the oxygen-containing functional groups on the surface, improve the loading stability of trace elements, and adjust the pH of the carbon-based materials to avoid high alkalinity inhibiting the growth of fermentation microorganisms. In addition, the carbon-based materials can adsorb nutrients in fertilizers, avoiding the loss of nutrients in fertilizers.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of fermentation fertilizer technology, specifically a method for producing growth-promoting and stress-resistant fertilizers by fermenting agricultural waste with carbon-based materials. Background Technology
[0002] Agricultural production generates a large amount of agricultural waste every year, such as straw, fruit and vegetable residues, and livestock and poultry manure. Randomly dumping, burning, or discarding these wastes not only causes serious environmental pollution but also leads to a significant waste of organic resources. Composting and fermenting agricultural waste into organic fertilizer is the core way to achieve its resource recycling and is in line with the development concepts of ecological and green agriculture. Carbon-based materials have the characteristics of porous and loose structure, large specific surface area, strong adsorption capacity, stable chemical properties, and excellent acid-base buffering capacity. They can adsorb and fix nutrients, reduce nutrient loss, and improve the physical and chemical properties of soil.
[0003] Fermented agricultural waste fertilizers, primarily composed of crop straw, are organic materials that have undergone fermentation and decomposition. These fermented materials effectively provide organic nutrients to crops. However, nutrients are easily lost during the fermentation process, resulting in low utilization rates of the fermented fertilizer. Adding carbon-based materials can adsorb and fix nutrients, reduce nutrient loss, and improve soil physicochemical properties. However, the addition of carbon-based materials to fermented agricultural waste is often a simple mixture without modification or activation of the carbon-based materials. This prevents the synergistic effects of the carbon-based materials from being realized, resulting in limited growth-promoting and stress-resistant properties in the prepared fertilizers. Summary of the Invention
[0004] This invention provides a method for producing growth-promoting and stress-resistant fertilizers by fermenting agricultural waste with carbon-based materials. This method solves the problems of easy nutrient loss, the simple mixing and addition of carbon-based materials and fermented agricultural waste without modification and activation of the carbon-based materials, which prevents the synergistic effects of the carbon-based materials from being realized and results in limited growth-promoting and stress-resistant properties of the prepared fertilizers.
[0005] The technical solution of this invention:
[0006] A carbon-based material-enhanced agricultural waste fermentation fertilizer for promoting growth and stress resistance includes the following raw materials in parts by weight: 30-40 parts biomass, 10-12 parts fermentation liquid, 20-30 parts composite carbon-based material, 25-35 parts inorganic fertilizer, 2-4 parts carboxymethyl cellulose, and 1-2 parts calcium chloride.
[0007] The composite carbon-based material is obtained by pyrolysis and carbonization of livestock waste, acidification, loading with chelated trace elements, and then mixing with an organic carbon source.
[0008] A method for producing growth-promoting and stress-resistant fertilizer by fermenting agricultural waste with carbon-based materials includes the following steps:
[0009] Biomass, composite carbon-based materials, carboxymethyl cellulose, and calcium chloride are premixed in a mixer for 10-15 minutes. The speed is set to 20-30 rpm, the vacuum degree is ≤-0.08 MPa, and the ambient humidity is ≤40%. Then, inorganic fertilizer is added and mixing continues for 5-10 minutes. Finally, fermentation liquid is added and mixing continues for 10-15 minutes to obtain a growth-promoting and stress-resistant fertilizer.
[0010] Further, the fermentation broth is specifically prepared by: inoculating the compound bacterial agent into the culture medium at an inoculation amount of 2-5%, culturing at 30-32℃ and 180-200rpm for 3-5 days, and collecting the fermentation product; diluting the fermentation product with deionized water to obtain the fermentation broth; the mass ratio of the fermentation product to deionized water is 1:(2-3).
[0011] Furthermore, the culture medium formula is as follows: glucose 15-20 g / L, corn starch 10-15 g / L, peptone 5-10 g / L, yeast extract 5-10 g / L, amino acids 8-10 g / L, magnesium sulfate 0.4-0.5 g / L, potassium dihydrogen phosphate 0.4-0.5 g / L, and the pH value of the culture medium is 7.0-7.2.
[0012] Furthermore, the compound bacterial agent is obtained by mixing Bacillus subtilis, Bacillus megaterium and Pseudomonas fluorescens in a live bacteria ratio of 1:1:(1-1.2).
[0013] Furthermore, the biomass material is a mixture of poultry and livestock manure, corn stalk powder, and rice stalk powder in a mass ratio of 1:1:(0.5-0.7).
[0014] Furthermore, the inorganic fertilizer is obtained by mixing potassium dihydrogen phosphate, ammonium sulfate and monoammonium phosphate in a mass ratio of (2-4):(1-3):(3-5).
[0015] Furthermore, the composite carbon-based material is specifically prepared by the following steps:
[0016] A1. Dry livestock waste to a moisture content of 8-10%, crush and sieve it to control the particle size of 1-2 mm. Treat the obtained product at a heating rate of 8-10℃ / min at 150-160℃ under a nitrogen atmosphere for 60-70 min. Then raise the system temperature to 500-520℃ at a heating rate of 4-5℃ / min and continue to treat for 90-100 min to obtain carbon-based materials.
[0017] The pyrolytic carbon-based material is mixed with an 8 mol / L nitric acid solution and stirred at 45-55℃ for 4-5 hours and at 85-95℃ for 2-3 hours. After filtration, washing, and drying, activated carbon-based material is obtained.
[0018] A2. The chelated trace elements are prepared by mixing zinc disodium ethylenediaminetetraacetate, ferric citrate, boric acid, and deionized water in a mass ratio of (0.15-0.2):(0.1-0.15):(0.15-0.2):100. The chelated trace elements are mixed with activated carbon-based materials and stirred and adsorbed at -0.08~-0.12 MPa for 30-40 min. The mixture is then dried until the moisture evaporates to obtain the modified carbon-based material.
[0019] A3. The organic carbon source is composed of glucose, sucrose, maltose and starch in a mass ratio of 1:1:1:(2-2.2). The organic carbon source and ethanol are mixed and stirred to dissolve. Modified carbon-based material is added and stirred and adsorbed at -0.08~-0.12MPa for 30-40min. The mixture is then dried until the ethanol evaporates to obtain the composite carbon-based material.
[0020] Furthermore, in the A1 reaction process described above, livestock waste undergoes pyrolysis, carbonization, and acidification. By pre-drying the livestock waste, the interference of water vapor during pyrolysis is reduced, allowing the pyrolysis reaction to focus more on the decomposition of organic matter and promoting mesopore formation. Subsequently, a two-step heat treatment is performed, with a high heating rate combined with a reaction temperature of 150-250℃ to accelerate the uniformity of the pyrolysis reaction, promote the rapid release of volatiles, and form more pore channels. At 500-550℃, the high temperature promotes the orderly arrangement of carbon atoms to form a layered structure, and the interlayer voids form mesopores. At the same time, some inorganic matter is converted into ash at high temperature to fill the micropores and enhance the stability of the particle structure and pores.
[0021] The resulting carbon-based material is acidified. Nitric acid, as a strong oxidant, attacks the unsaturated carbon atoms in the carbon layer on the surface of the carbon-based material, converting the CH bonds and C=C bonds on the carbon layer into CO bonds, thereby introducing polar oxygen-containing groups on the surface of the carbon-based material to obtain activated carbon-based material.
[0022] Furthermore, in the A2 reaction process described above, the activated carbon-based material has a high porosity, which enables the chelated trace elements to be adsorbed into the pores of the activated carbon-based material, thus obtaining the modified carbon-based material.
[0023] Furthermore, in the A3 reaction process described above, the organic carbon source is composed of glucose, sucrose, maltose, and starch mixed in a mass ratio of 1:1:1:(2-2.2). The organic carbon source is soluble in deionized water and has a high binding effect. The residual porous structure in the modified carbon-based material can adsorb the organic carbon source onto the surface of the modified carbon-based material, and the organic carbon source can penetrate into the porous structure of the modified carbon-based material, so that the pores of the modified carbon-based material contain chelated trace elements and organic carbon source, thus obtaining a composite carbon-based material.
[0024] Further, in step A1, the mass ratio of the pyrolytic carbon-based material to the nitric acid solution is 1:(40-45).
[0025] Further, in step A2, the mass ratio of the chelated trace elements to the activated carbon-based material is (80-100):1.
[0026] Further, in step A3, the mass ratio of the organic carbon source, ethanol, and modified carbon-based material is (0.1-0.15):(80-100):1.
[0027] The present invention has the following beneficial effects:
[0028] (1) In the technical solution of the present invention, the pyrolysis and carbonization of livestock waste and acidification form activated carbon-based materials. On the one hand, the activated carbon-based materials have a high porosity structure, which serves as adsorption sites for chelated trace elements. The chelated trace elements are loaded onto the activated carbon-based materials, avoiding the direct addition of chelated trace elements to fertilizers, which are prone to migration and precipitation, affecting the growth-promoting and stress-resistant effects of fertilizers. On the other hand, the carbon-based materials are acidified to remove inorganic ash and heavy metal impurities inside the biochar, clear the microporous structure, increase the oxygen-containing functional groups on the surface, improve the loading stability of trace elements, and adjust the pH of the carbon-based materials to avoid high alkalinity inhibiting the growth of fermentation microorganisms. In addition, the carbon-based materials can adsorb nutrients in fertilizers, avoiding the loss of nutrients in fertilizers.
[0029] (2) In the technical solution of the present invention, chelated trace elements are adsorbed in the pores of activated carbon-based material. The chelated trace elements include zinc, iron and boron, which can participate in the activity of enzymes in plants, regulate plant metabolism, maintain cell structure and functional stability, and improve fertilizer fertility. Furthermore, adsorbing chelated trace elements in the pores of activated carbon-based material enhances the role of chelated trace elements in fertilizer and avoids the direct addition of chelated trace elements to fertilizer, which is prone to migration and precipitation, affecting the growth-promoting and stress-resistant effects of fertilizer.
[0030] (3) In the technical solution of the present invention, the organic carbon source permeates into the porous structure of the modified carbon-based material, so that the pores of the modified carbon-based material contain chelated trace elements and organic carbon source. As a composite carbon-based material, on the one hand, the organic carbon source fills the modified carbon-based material and seals the pores of the modified carbon-based material. In the early stage of fermentation, it avoids the adsorption of organic matter, small molecule carbon source and microbial substrate in the fermentation system by the carbon-based material, which leads to carbon deficiency, decreased activity and slowed decomposition of fermenting bacteria, affecting the fertility of fertilizer. On the other hand, as fermentation proceeds, the organic carbon source in the composite carbon-based material provides nutrition for fermentation. The organic carbon source is consumed and decomposed, providing a large amount of carbon source for fermentation, improving fermentation efficiency and enhancing the fertility of fertilizer. In addition, the decomposition of the organic carbon source in the composite carbon-based material causes the chelated trace elements in the composite carbon-based material to be released slowly, increasing the trace element content of fertility and enhancing the fertility of fertilizer.
[0031] (4) In the technical solution of the present invention, the growth-promoting and stress-resistant fertilizer prepared by mixing biomass materials, composite carbon-based materials, carboxymethyl cellulose and calcium chloride, inorganic fertilizer and fermentation liquid has high fertility and can reduce nutrient loss. Detailed Implementation
[0032] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0033] The raw materials used in the embodiments of this invention are shown below, and all reagents used are analytical grade.
[0034] Among them, livestock waste includes duck feathers.
[0035] Bacillus subtilis (CICC 10161); Pseudomonas fluorescens (CICC 23919); Bacillus megaterium (CICC23692).
[0036] Carboxymethyl cellulose, product number C804618, is manufactured by Shanghai Maclean Biochemical Technology Co., Ltd.
[0037] The starch is corn starch.
[0038] Example 1
[0039] A carbon-based material-enhanced agricultural waste fermentation fertilizer for promoting growth and stress resistance includes the following raw materials in parts by weight: 30 parts biomass, 10 parts fermentation liquid, 20 parts composite carbon-based material, 25 parts inorganic fertilizer, 2 parts carboxymethyl cellulose, and 1 part calcium chloride.
[0040] A method for preparing a growth-promoting and stress-resistant fertilizer from the fermentation of agricultural waste reinforced with carbon-based materials includes the following steps:
[0041] Biomass, composite carbon-based materials, carboxymethyl cellulose, and calcium chloride were premixed in a mixer for 10 minutes at a speed of 20 rpm, a vacuum of -0.1 MPa, and an ambient humidity of 30%. Inorganic fertilizer was then added, and the mixture was mixed for another 5 minutes. Fermentation liquid was then added, and the mixture was mixed for another 10 minutes to obtain a growth-promoting and stress-resistant fertilizer.
[0042] The biomass feed is made by mixing poultry and livestock manure, corn stalk powder, and rice stalk powder in a mass ratio of 1:1:0.5; the inorganic fertilizer is made by mixing potassium dihydrogen phosphate, ammonium sulfate, and monoammonium phosphate in a mass ratio of 2:1:3.
[0043] The fermentation broth is prepared as follows: the compound bacterial agent is inoculated into the culture medium at an inoculation amount of 2%, and cultured at 30℃ and 180 rpm for 3 days. The fermentation product is then collected. The fermentation product is diluted with deionized water to obtain the fermentation broth. The mass ratio of fermentation product to deionized water is 1:2.
[0044] The culture medium formula is as follows: glucose 15g / L, corn starch 10g / L, peptone 5g / L, yeast extract 5g / L, amino acids 8g / L, magnesium sulfate 0.4g / L, potassium dihydrogen phosphate 0.4g / L, and the pH value of the culture medium is 7.0.
[0045] The compound microbial agent is prepared by mixing Bacillus subtilis, Bacillus megaterium and Pseudomonas fluorescens in a live bacteria ratio of 1:1:1.
[0046] Composite carbon-based materials are prepared by the following steps:
[0047] A1. Dry duck feathers at 80℃ to a moisture content of 8%, crush and sieve them, control the particle size to 1mm, and treat the obtained product at 150℃ and nitrogen atmosphere at a heating rate of 8℃ / min for 60min. Then, increase the system temperature to 500℃ at a heating rate of 4℃ / min and continue to treat for 90min to obtain carbon-based material.
[0048] The pyrolytic carbon-based material was mixed with an 8 mol / L nitric acid solution and stirred at 45°C for 4 h and then at 85°C for 2 h. After filtration, the mixture was washed with deionized water until the pH of the washing solution was neutral and then dried in an oven at 90°C for 30 min to obtain the activated carbon-based material. The mass ratio of the pyrolytic carbon-based material to the nitric acid solution was 1:40.
[0049] A2. The chelated trace elements were prepared by mixing zinc disodium ethylenediaminetetraacetate, ferric citrate, boric acid, and deionized water in a mass ratio of 0.15:0.1:0.15:100. The chelated trace elements were mixed with activated carbon-based materials and stirred for adsorption at -0.08 MPa for 30 min. The mixture was then dried in a 90℃ oven until all moisture was evaporated to obtain the modified carbon-based material. The mass ratio of chelated trace elements to activated carbon-based materials was 80:1.
[0050] A3. The organic carbon source is composed of glucose, sucrose, maltose, and corn starch in a mass ratio of 1:1:1:2. The organic carbon source is added to ethanol and stirred until completely dissolved. Modified carbon-based material is then added, and the mixture is stirred and adsorbed at -0.08 MPa for 30 min. The mixture is then dried in a 90℃ oven until the ethanol is completely evaporated to obtain the composite carbon-based material. The mass ratio of organic carbon source, ethanol, and modified carbon-based material is 0.1:80:1.
[0051] Example 2
[0052] A carbon-based material-enhanced agricultural waste fermentation fertilizer for promoting growth and stress resistance includes the following raw materials in parts by weight: 35 parts biomass, 11 parts fermentation liquid, 25 parts composite carbon-based material, 30 parts inorganic fertilizer, 3 parts carboxymethyl cellulose, and 1.5 parts calcium chloride.
[0053] A method for preparing a growth-promoting and stress-resistant fertilizer from the fermentation of agricultural waste reinforced with carbon-based materials includes the following steps:
[0054] Biomass, composite carbon-based materials, carboxymethyl cellulose, and calcium chloride were premixed in a mixer for 13 minutes at a speed of 25 rpm, a vacuum of -0.1 MPa, and an ambient humidity of 30%. Inorganic fertilizer was then added, and the mixture was mixed for another 8 minutes. Fermentation liquid was then added, and the mixture was mixed for another 13 minutes to obtain a growth-promoting and stress-resistant fertilizer.
[0055] The biomass material is a mixture of poultry and livestock manure, corn stalk powder, and rice stalk powder in a mass ratio of 1:1:0.6; the inorganic fertilizer is a mixture of potassium dihydrogen phosphate, ammonium sulfate, and monoammonium phosphate in a mass ratio of 3:2:4.
[0056] The fermentation broth is prepared as follows: the compound bacterial agent is inoculated into the culture medium at an inoculation amount of 3%, and cultured at 31℃ and 190 rpm for 4 days. The fermentation product is then collected. The fermentation product is diluted with deionized water to obtain the fermentation broth. The mass ratio of fermentation product to deionized water is 1:2.5.
[0057] The culture medium formula is as follows: glucose 18g / L, corn starch 13g / L, peptone 8g / L, yeast extract 8g / L, amino acids 9g / L, magnesium sulfate 0.45g / L, potassium dihydrogen phosphate 0.45g / L, and the pH value of the culture medium is 7.1.
[0058] The compound microbial agent is prepared by mixing Bacillus subtilis, Bacillus megaterium and Pseudomonas fluorescens in a live cell ratio of 1:1:1.1.
[0059] Composite carbon-based materials are prepared by the following steps:
[0060] A1. Duck feathers were dried at 80℃ to a moisture content of 9%, crushed and sieved to control the particle size of 1.5mm. The resulting product was treated at 155℃ and under nitrogen atmosphere at a heating rate of 9℃ / min for 65min. Then, the system temperature was increased to 510℃ at a heating rate of 4.5℃ / min and the treatment was continued for 95min to obtain carbon-based material.
[0061] The pyrolytic carbon-based material was mixed with an 8 mol / L nitric acid solution and stirred at 50°C for 4.5 h and at 90°C for 2.5 h. After filtration, the mixture was washed with deionized water until the pH of the washing solution was neutral and then dried in a 90°C oven for 30 min to obtain the activated carbon-based material. The mass ratio of the pyrolytic carbon-based material to the nitric acid solution was 1:43.
[0062] A2. The chelated trace elements were prepared by mixing zinc disodium ethylenediaminetetraacetate, ferric citrate, boric acid, and deionized water in a mass ratio of 0.18:0.13:0.18:100. The chelated trace elements were mixed with activated carbon-based materials and stirred for adsorption at -0.1 MPa for 35 min. The mixture was then dried in a 90℃ oven until all moisture was evaporated to obtain the modified carbon-based material. The mass ratio of chelated trace elements to activated carbon-based materials was 90:1.
[0063] A3. The organic carbon source is composed of glucose, sucrose, maltose, and corn starch mixed in a mass ratio of 1:1:1:2.1. The organic carbon source is added to ethanol and stirred until completely dissolved. Modified carbon-based material is then added, and the mixture is stirred and adsorbed at -0.1 MPa for 35 min. The mixture is then dried in a 90℃ oven until the ethanol is completely evaporated to obtain the composite carbon-based material. The mass ratio of organic carbon source, ethanol, and modified carbon-based material is 0.13:90:1.
[0064] Example 3
[0065] A carbon-based material-enhanced agricultural waste fermentation fertilizer for promoting growth and stress resistance includes the following raw materials in parts by weight: 40 parts biomass, 12 parts fermentation liquid, 30 parts composite carbon-based material, 35 parts inorganic fertilizer, 4 parts carboxymethyl cellulose, and 2 parts calcium chloride.
[0066] A method for preparing a growth-promoting and stress-resistant fertilizer from the fermentation of agricultural waste reinforced with carbon-based materials includes the following steps:
[0067] Biomass, composite carbon-based materials, carboxymethyl cellulose, and calcium chloride were premixed in a mixer for 15 minutes. The speed was set to 30 rpm, the vacuum degree to -0.08 MPa, and the ambient humidity to 40%. Inorganic fertilizer was then added, and the mixture was mixed for another 10 minutes. Fermentation liquid was then added, and the mixture was mixed for another 15 minutes to obtain a growth-promoting and stress-resistant fertilizer.
[0068] The biomass material is a mixture of poultry and livestock manure, corn stalk powder, and rice stalk powder in a mass ratio of 1:1:0.7; the inorganic fertilizer is a mixture of potassium dihydrogen phosphate, ammonium sulfate, and monoammonium phosphate in a mass ratio of 4:3:5.
[0069] The fermentation broth is prepared as follows: the compound bacterial agent is inoculated into the culture medium at an inoculation amount of 5%, and cultured at 32℃ and 200rpm for 5 days. The fermentation product is then collected. The fermentation product is diluted with deionized water to obtain the fermentation broth. The mass ratio of fermentation product to deionized water is 1:3.
[0070] The culture medium formula is as follows: glucose 20 g / L, corn starch 15 g / L, peptone 10 g / L, yeast extract 10 g / L, amino acids 10 g / L, magnesium sulfate 0.5 g / L, potassium dihydrogen phosphate 0.5 g / L, and the pH value of the culture medium is 7.2.
[0071] The compound microbial agent is prepared by mixing Bacillus subtilis, Bacillus megaterium and Pseudomonas fluorescens in a viable cell ratio of 1:1:1.2.
[0072] Composite carbon-based materials are prepared by the following steps:
[0073] A1. Dry duck feathers at 80℃ to a moisture content of 10%, crush and sieve them, control the particle size to 2mm, and treat the obtained product at 160℃ and nitrogen atmosphere at a heating rate of 10℃ / min for 70min. Then, increase the system temperature to 520℃ at a heating rate of 5℃ / min and continue to treat for 100min to obtain carbon-based material.
[0074] The pyrolytic carbon-based material was mixed with an 8 mol / L nitric acid solution and stirred at 55°C for 5 h and then at 95°C for 3 h. After filtration, the mixture was washed with deionized water until the pH of the washing solution was neutral and then dried in an oven at 90°C for 30 min to obtain the activated carbon-based material. The mass ratio of the pyrolytic carbon-based material to the nitric acid solution was 1:45.
[0075] A2. The chelated trace elements were prepared by mixing zinc disodium ethylenediaminetetraacetate, ferric citrate, boric acid, and deionized water in a mass ratio of 0.2:0.15:0.2:100. The chelated trace elements were mixed with activated carbon-based materials and stirred for adsorption at -0.12 MPa for 40 min. The mixture was then dried in a 90℃ oven until all moisture was evaporated to obtain the modified carbon-based material. The mass ratio of chelated trace elements to activated carbon-based materials was 100:1.
[0076] A3. The organic carbon source is composed of glucose, sucrose, maltose, and corn starch in a mass ratio of 1:1:1:2.2. The organic carbon source is added to ethanol and stirred until completely dissolved. Modified carbon-based material is then added, and the mixture is stirred and adsorbed at -0.12 MPa for 40 min. The mixture is then dried in a 90℃ oven until the ethanol is completely evaporated to obtain the composite carbon-based material. The mass ratio of organic carbon source, ethanol, and modified carbon-based material is 0.15:100:1.
[0077] Comparative Example 1
[0078] The only difference between this comparative example and Example 3 is the preparation of the composite carbon-based material, as detailed below:
[0079] Composite carbon-based materials are prepared by the following steps:
[0080] A1. Dry duck feathers at 80℃ to a moisture content of 10%, crush and sieve them, control the particle size to 2mm, and treat the obtained product at 160℃ and nitrogen atmosphere at a heating rate of 10℃ / min for 70min. Then, increase the system temperature to 520℃ at a heating rate of 5℃ / min and continue to treat for 100min to obtain carbon-based material.
[0081] A2. The chelated trace elements were prepared by mixing zinc disodium ethylenediaminetetraacetate, ferric citrate, boric acid, and deionized water in a mass ratio of 0.2:0.15:0.2:100. The chelated trace elements were mixed with carbon-based materials and stirred for adsorption at -0.12 MPa for 40 min. The mixture was then dried in a 90℃ oven until all moisture was evaporated to obtain the modified carbon-based material. The mass ratio of chelated trace elements to carbon-based materials was 100:1.
[0082] A3. The organic carbon source is composed of glucose, sucrose, maltose, and corn starch in a mass ratio of 1:1:1:2.2. The organic carbon source is added to ethanol and stirred until completely dissolved. Modified carbon-based material is then added, and the mixture is stirred and adsorbed at -0.12 MPa for 40 min. The mixture is then dried in a 90℃ oven until the ethanol is completely evaporated to obtain the composite carbon-based material. The mass ratio of organic carbon source, ethanol, and modified carbon-based material is 0.15:100:1.
[0083] Comparative Example 2
[0084] The only difference between this comparative example and Example 3 is the preparation of the composite carbon-based material, as detailed below:
[0085] Composite carbon-based materials are prepared by the following steps:
[0086] A1. The chelated trace elements were prepared by mixing zinc disodium ethylenediaminetetraacetate, ferric citrate, boric acid, and deionized water in a mass ratio of 0.2:0.15:0.2:100. The chelated trace elements were mixed with duck feathers and stirred for adsorption at -0.12 MPa for 40 min. The mixture was then dried in a 90℃ oven until all moisture was evaporated to obtain the modified carbon-based material. The mass ratio of chelated trace elements to duck feathers was 100:1.
[0087] A2. The organic carbon source is composed of glucose, sucrose, maltose, and corn starch in a mass ratio of 1:1:1:2.2. The organic carbon source is added to ethanol and stirred until completely dissolved. Modified carbon-based material is then added, and the mixture is stirred and adsorbed at -0.12 MPa for 40 min. The mixture is then dried in a 90℃ oven until the ethanol is completely evaporated to obtain the composite carbon-based material. The mass ratio of organic carbon source, ethanol, and modified carbon-based material is 0.15:100:1.
[0088] Comparative Example 3
[0089] The only difference between this comparative example and Example 3 is the preparation of the composite carbon-based material, as detailed below:
[0090] Composite carbon-based materials are prepared by the following steps:
[0091] A1. Dry duck feathers at 80℃ to a moisture content of 10%, crush and sieve them, control the particle size to 2mm, and treat the obtained product at 160℃ and nitrogen atmosphere at a heating rate of 10℃ / min for 70min. Then, increase the system temperature to 520℃ at a heating rate of 5℃ / min and continue to treat for 100min to obtain carbon-based material.
[0092] The pyrolytic carbon-based material was mixed with an 8 mol / L nitric acid solution and stirred at 55°C for 5 h and then at 95°C for 3 h. After filtration, the mixture was washed with deionized water until the pH of the washing solution was neutral and then dried in an oven at 90°C for 30 min to obtain the activated carbon-based material. The mass ratio of the pyrolytic carbon-based material to the nitric acid solution was 1:45.
[0093] A2. The chelated trace elements were prepared by mixing ferric citrate, boric acid, and deionized water in a mass ratio of 0.35:0.2:100. The chelated trace elements were mixed with activated carbon-based materials and stirred for adsorption at -0.12 MPa for 40 min. The mixture was then dried in a 90℃ oven until all moisture was evaporated to obtain the modified carbon-based material. The mass ratio of chelated trace elements to activated carbon-based materials was 100:1.
[0094] A3. The organic carbon source is composed of glucose, sucrose, maltose, and corn starch in a mass ratio of 1:1:1:2.2. The organic carbon source is added to ethanol and stirred until completely dissolved. Modified carbon-based material is then added, and the mixture is stirred and adsorbed at -0.12 MPa for 40 min. The mixture is then dried in a 90℃ oven until the ethanol is completely evaporated to obtain the composite carbon-based material. The mass ratio of organic carbon source, ethanol, and modified carbon-based material is 0.15:100:1.
[0095] Comparative Example 4
[0096] The only difference between this comparative example and Example 3 is the preparation of the composite carbon-based material, as detailed below:
[0097] Composite carbon-based materials are prepared by the following steps:
[0098] A1. Dry duck feathers at 80℃ to a moisture content of 10%, crush and sieve them, control the particle size to 2mm, and treat the obtained product at 160℃ and nitrogen atmosphere at a heating rate of 10℃ / min for 70min. Then, increase the system temperature to 520℃ at a heating rate of 5℃ / min and continue to treat for 100min to obtain carbon-based material.
[0099] The pyrolytic carbon-based material was mixed with an 8 mol / L nitric acid solution and stirred at 55°C for 5 h and then at 95°C for 3 h. After filtration, the mixture was washed with deionized water until the pH of the washing solution was neutral and then dried in an oven at 90°C for 30 min to obtain the activated carbon-based material. The mass ratio of the pyrolytic carbon-based material to the nitric acid solution was 1:45.
[0100] A2. The chelated trace elements were prepared by mixing zinc disodium ethylenediaminetetraacetate, boric acid, and deionized water in a mass ratio of 0.2:0.35:100. The chelated trace elements were mixed with activated carbon-based materials and stirred for adsorption at -0.12 MPa for 40 min. The mixture was then dried in a 90℃ oven until all moisture was evaporated to obtain the modified carbon-based material. The mass ratio of chelated trace elements to activated carbon-based materials was 100:1.
[0101] A3. The organic carbon source is composed of glucose, sucrose, maltose, and corn starch in a mass ratio of 1:1:1:2.2. The organic carbon source is added to ethanol and stirred until completely dissolved. Modified carbon-based material is then added, and the mixture is stirred and adsorbed at -0.12 MPa for 40 min. The mixture is then dried in a 90℃ oven until the ethanol is completely evaporated to obtain the composite carbon-based material. The mass ratio of organic carbon source, ethanol, and modified carbon-based material is 0.15:100:1.
[0102] Comparative Example 5
[0103] The only difference between this comparative example and Example 3 is the preparation of the composite carbon-based material, as detailed below:
[0104] Composite carbon-based materials are prepared by the following steps:
[0105] A1. Dry duck feathers at 80℃ to a moisture content of 10%, crush and sieve them, control the particle size to 2mm, and treat the obtained product at 160℃ and nitrogen atmosphere at a heating rate of 10℃ / min for 70min. Then, increase the system temperature to 520℃ at a heating rate of 5℃ / min and continue to treat for 100min to obtain carbon-based material.
[0106] The pyrolytic carbon-based material was mixed with an 8 mol / L nitric acid solution and stirred at 55°C for 5 h and then at 95°C for 3 h. After filtration, the mixture was washed with deionized water until the pH of the washing solution was neutral and then dried in an oven at 90°C for 30 min to obtain the activated carbon-based material. The mass ratio of the pyrolytic carbon-based material to the nitric acid solution was 1:45.
[0107] A2. The chelated trace elements were prepared by mixing zinc disodium ethylenediaminetetraacetate, ferric citrate, boric acid, and deionized water in a mass ratio of 0.2:0.15:0.2:100. The chelated trace elements were mixed with activated carbon-based materials and stirred for adsorption at -0.12 MPa for 40 min. The mixture was then dried in a 90℃ oven until all moisture was evaporated to obtain the modified carbon-based material. The mass ratio of chelated trace elements to activated carbon-based materials was 100:1.
[0108] A3. The organic carbon source is a mixture of glucose, sucrose, and maltose in a mass ratio of 3.2:1:1. The organic carbon source is added to ethanol and stirred until completely dissolved. Modified carbon-based material is then added, and the mixture is stirred and adsorbed at -0.12 MPa for 40 min. The mixture is then dried in a 90℃ oven until the ethanol is completely evaporated, yielding a composite carbon-based material. The mass ratio of organic carbon source, ethanol, and modified carbon-based material is 0.15:100:1.
[0109] Comparative Example 6
[0110] The only difference between this comparative example and Example 3 is the preparation of the composite carbon-based material, as detailed below:
[0111] Composite carbon-based materials are prepared by the following steps:
[0112] A1. Dry duck feathers at 80℃ to a moisture content of 10%, crush and sieve them, control the particle size to 2mm, and treat the obtained product at 160℃ and nitrogen atmosphere at a heating rate of 10℃ / min for 70min. Then, increase the system temperature to 520℃ at a heating rate of 5℃ / min and continue to treat for 100min to obtain carbon-based material.
[0113] The pyrolytic carbon-based material was mixed with an 8 mol / L nitric acid solution and stirred at 55°C for 5 h and then at 95°C for 3 h. After filtration, the mixture was washed with deionized water until the pH of the washing solution was neutral and then dried in an oven at 90°C for 30 min to obtain the activated carbon-based material. The mass ratio of the pyrolytic carbon-based material to the nitric acid solution was 1:45.
[0114] A2. The chelated trace elements were prepared by mixing zinc disodium ethylenediaminetetraacetate, ferric citrate, boric acid, and deionized water in a mass ratio of 0.2:0.15:0.2:100. The chelated trace elements were mixed with activated carbon-based materials and stirred for adsorption at -0.12 MPa for 40 min. The mixture was then dried in a 90℃ oven until all moisture was evaporated to obtain the modified carbon-based material. The mass ratio of chelated trace elements to activated carbon-based materials was 100:1.
[0115] A3. The organic carbon source is composed of glucose, sucrose, maltose and corn starch in a mass ratio of 1:1:1:2.2. The organic carbon source and the modified carbon-based material are mixed to obtain the composite carbon-based material; the mass ratio of organic carbon source, ethanol and modified carbon-based material is 0.15:100:1.
[0116] The performance of the growth-promoting and stress-resistant fertilizers prepared in Examples 1-3 and Comparative Examples 1-6 was tested.
[0117] The above-prepared growth-promoting and stress-resistant fertilizer was mixed with the soil at a rate of 0.5 g / kg. The soil moisture content was adjusted to 60% of field capacity with deionized water. The mixture was then transferred to a culture bottle and placed in a 36°C constant temperature incubator for 30 days. During this period, water was added every 4 days using a weighing method to maintain the soil moisture content at 60% of field capacity. After cultivation, soil samples were collected, and the total nitrogen content, available phosphorus content, potassium content, and organic matter content in the soil were determined.
[0118] The total nitrogen content of the prepared organic-inorganic compound fertilizer was determined using GB / T8572-2010 "Determination of Total Nitrogen Content in Compound Fertilizers - Distillation Titration Method"; the available phosphorus content in the compound fertilizer was determined using GB / T8573-2017 "Determination of Available Phosphorus Content in Compound Fertilizers"; the potassium content in the compound fertilizer was determined using GB / T8574-2024 "Determination of Potassium Content in Compound Fertilizers"; and the organic matter content in the compound fertilizer was determined using NY / T525-2021 "Determination of Organic Fertilizers".
[0119] Field planting experiment: The above-prepared growth-promoting and stress-resistant fertilizer was spread on the soil and then plowed into the soil. Corn and wheat were planted in the experimental plots where the fertilizer was applied. The field water, fertilizer and management conditions were uniform. The plants were managed according to routine conditions during the growing season and harvested after 120 days. The yield (kg / mu) was calculated. The amount of fertilizer applied was 240 kg per mu.
[0120] The fertilizer's stress resistance was demonstrated by measuring the yields of corn and wheat grown under conditions of drought, high temperature, low temperature, salinity, pests, and lodging. The specific procedures are as follows:
[0121] Arid-condition planting experiment: By controlling rainfall through a water-covered greenhouse, the relative soil moisture content was maintained at 40-50% of field capacity (drought stress) for 30 days. Planting was then conducted using the above field planting method, and harvesting was carried out after 120 days. Yield (kg / mu) was calculated. Fertilizer application was 240 kg / mu. Yield loss rate (%) was calculated as: (Field crop yield - Arid-condition crop yield) / Field crop yield × 100%.
[0122] High-temperature and low-temperature planting experiments: High-temperature planting was conducted by maintaining field temperatures at 35-40℃, nighttime temperatures ≥25℃, and relative humidity 60-70% in a temperature-controlled greenhouse for 15 days. Low-temperature planting was conducted by maintaining temperatures at 5-10℃, light intensity 12h / d, and relative humidity 60-70% for 7 days. Planting was carried out using these methods, and harvesting was conducted after 120 days. Yields (kg / mu) were calculated. Fertilizer application was 240 kg / mu. Yield loss rate (%) was calculated as follows: (Yield of field crop - Yield of crop grown under high-temperature conditions) / Yield of field crop × 100%; Yield loss rate (%) was calculated as follows: (Yield of field crop - Yield of crop grown under low-temperature conditions) / Yield of field crop × 100%.
[0123] Planting experiment under pest conditions: During the crop's sensitive period for pests, target pests (such as aphids, corn borers, and cotton bollworms) were artificially inoculated, and the pest population density was controlled at 50 insects / plant. The crops were planted using the above field planting experiment method, and harvested after 120 days. The yield (kg / mu) was calculated. The fertilizer application rate was 240 kg / mu. The yield loss rate (%) was calculated as follows: (yield of field-planted crops - yield of crops planted under pest conditions) / yield of field-planted crops × 100%.
[0124] Planting experiment under saline-alkali conditions: Using a saline-alkali soil mix (NaCl:Na2SO4 = 1:1 molar ratio), the soil salinity was controlled at 0.5%. The crops were planted until maturity using the above field planting experiment method. The yield loss rate (%) was calculated as follows: (Field crop yield - Crops grown under saline-alkali conditions) / Field crop yield × 100%.
[0125] Planting experiment under lodging conditions: A mobile fan and a rooftop sprinkler system were used to simulate wind and rain. Water was pre-sprayed for 5 minutes before treatment, with a total spray flow rate of 5 m³ / h. 3 / h, then the fan nozzle is aimed at the ear position at a 30° angle with the planting row, and water is sprayed continuously at a wind speed of 14m / s for 60 minutes to simulate a level 6-7 wind and rain disaster; after treatment, the crops naturally recover and are planted to maturity using the above field planting experiment method, with the lodging rate controlled at 40%. The yield loss rate (%) is calculated as follows: (yield of field-planted crops - yield of crops planted under lodging conditions) / yield of field-planted crops × 100%.
[0126] The test results are shown in Table 1.
[0127] Table 1. Performance testing of growth-promoting and stress-resistance fertilizers prepared in Examples 1-3 and Comparative Examples 1-6
[0128]
[0129] Table 2. Performance testing of growth-promoting and stress-resistant fertilizers prepared in Examples 1-3 and Comparative Examples 1-6
[0130]
[0131] Table 3. Performance testing of the growth-promoting and stress-resistance fertilizers prepared in Examples 1-3 and Comparative Examples 1-6
[0132]
[0133] Table 4. Performance testing of the growth-promoting and stress-resistance fertilizers prepared in Examples 1-3 and Comparative Examples 1-6
[0134]
[0135] As can be seen from the data in Tables 1, 2, 3 and 4, the growth-promoting and stress-resistant fertilizers prepared in Examples 1-3 have high fertility and can reduce nutrient loss.
[0136] Comparative Example 1 replaced the activated carbon-based material with a carbon-based material, and Comparative Example 2 replaced the activated carbon-based material with a composite carbon-based material prepared from duck feathers. When these materials were added to a growth-promoting and stress-resistant fertilizer, the yields of wheat and corn decreased, and the nutrient content in the soil also decreased. This demonstrates that the activated carbon-based material formed by the pyrolysis, carbonization, and acidification of livestock waste has a high porosity structure, serving as adsorption sites for chelated trace elements. Loading chelated trace elements onto the activated carbon-based material avoids the direct addition of chelated trace elements to the fertilizer, which is prone to migration and precipitation, thus affecting the growth-promoting and stress-resistant effects of the fertilizer. Furthermore, the acidification treatment of the carbon-based material removes inorganic ash and heavy metal impurities from the biochar, opens up the microporous structure, increases the surface oxygen-containing functional groups, improves the loading stability of trace elements, and regulates the pH of the carbon-based material, avoiding high alkalinity that inhibits the growth of fermenting microorganisms. In addition, the carbon-based material can adsorb nutrients in the fertilizer, preventing the loss of nutrients from the fertilizer.
[0137] Comparative Example 3, where zinc disodium ethylenediaminetetraacetate was replaced by ferric citrate, and Comparative Example 4, where ferric citrate was replaced by boric acid, showed that when these composite carbon-based materials were added to growth-promoting and stress-resistant fertilizers, the yields of wheat and corn decreased, and the nutrient composition of the soil also decreased. This demonstrates that adsorbing chelated trace elements into the pores of activated carbon-based materials—including zinc, iron, and boron—can participate in the activity of enzymes in plants, regulate plant metabolism, and maintain the stability of cell structure and function, thus improving fertilizer fertility. Furthermore, adsorbing chelated trace elements into the pores of activated carbon-based materials enhances their effectiveness in fertilizers, preventing direct addition of chelated trace elements from migrating and precipitating, which would negatively impact the growth-promoting and stress-resistant effects of the fertilizer. Utilizing the decomposition forces of organic carbon sources allows for the slow release of chelated trace elements from the composite carbon-based materials, increasing the trace element content and enhancing fertilizer fertility.
[0138] Comparative Example 5 showed that when a composite carbon-based material prepared by replacing corn starch with glucose was added to a growth-promoting and stress-resistant fertilizer, the yields of wheat and corn decreased, and the nutrient composition of the soil also decreased. This demonstrates that the organic carbon source is a mixture of glucose, sucrose, maltose, and starch. The organic carbon source is soluble in deionized water and has a high binding effect. The residual porous structure in the modified carbon-based material can adsorb the organic carbon source onto the surface of the modified carbon-based material, and the organic carbon source can penetrate into the porous structure of the modified carbon-based material, blocking the pores of the modified carbon-based material. This prevents the carbon-based material from adsorbing organic matter, small molecule carbon sources, and microbial substrates in the fermentation system, which would lead to carbon deficiency, decreased activity, and slower decomposition of the fermenting bacteria, thus affecting the fertility of the fertilizer.
[0139] Comparative Example 6: When a composite carbon-based material prepared from an unencapsulated organic carbon source was added to a growth-promoting and stress-resistant fertilizer, the yields of wheat and corn decreased, and the nutrient composition of the soil also decreased. This demonstrates that the organic carbon source penetrates into the porous structure of the modified carbon-based material, resulting in chelated trace elements and organic carbon sources within the pores of the modified carbon-based material. The organic carbon source fills the modified carbon-based material, sealing its pores. In the early stages of fermentation, this prevents the carbon-based material from adsorbing organic matter, small-molecule carbon sources, and microbial substrates within the fermentation system, which would lead to carbon deficiency, decreased activity, and slower decomposition of the fermenting bacteria, thus affecting the fertilizer's fertility. Furthermore, as fermentation progresses, the organic carbon source in the composite carbon-based material provides nutrients for fermentation. The organic carbon source is consumed and decomposed, providing a large amount of carbon source for fermentation, improving fermentation efficiency, and enhancing the fertilizer's fertility. In addition, the decomposition of the organic carbon source in the composite carbon-based material results in the slow release of chelated trace elements, increasing the trace element content and enhancing the fertilizer's fertility.
[0140] In the description of this specification, the references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0141] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.
Claims
1. A carbon-based material-enhanced fertilizer for fermenting agricultural waste to promote growth and resist stress, characterized in that, The raw materials include the following parts by weight: 30-40 parts biomass, 10-12 parts fermentation liquid, 20-30 parts composite carbon-based material, 25-35 parts inorganic fertilizer, 2-4 parts carboxymethyl cellulose, and 1-2 parts calcium chloride. The composite carbon-based material is obtained by pyrolysis and carbonization of livestock waste, acidification, loading with chelated trace elements, and then mixing with an organic carbon source.
2. The carbon-based material-enhanced agricultural waste fermentation fertilizer for promoting growth and resisting stress as described in claim 1, characterized in that, The composite carbon-based material is prepared by the following steps: A1. Dry livestock waste to a moisture content of 8-10%, crush and sieve it to control the particle size of 1-2 mm. Treat the obtained product at a heating rate of 8-10℃ / min at 150-160℃ under a nitrogen atmosphere for 60-70 min. Then raise the system temperature to 500-520℃ at a heating rate of 4-5℃ / min and continue to treat for 90-100 min to obtain carbon-based materials. The pyrolytic carbon-based material is mixed with nitric acid solution and stirred at 45-55℃ for 4-5 hours and at 85-95℃ for 2-3 hours. After filtration, washing and drying, activated carbon-based material is obtained. A2. The chelated trace elements are prepared by mixing zinc disodium ethylenediaminetetraacetate, ferric citrate, boric acid, and deionized water in a mass ratio of (0.15-0.2):(0.1-0.15):(0.15-0.2):
100. The chelated trace elements are mixed with activated carbon-based materials and stirred and adsorbed at -0.08~-0.12 MPa for 30-40 min. The mixture is then dried until the moisture evaporates to obtain the modified carbon-based material. A3. The organic carbon source is composed of glucose, sucrose, maltose and starch in a mass ratio of 1:1:1:(2-2.2). The organic carbon source and ethanol are mixed and stirred to dissolve. Modified carbon-based material is added and stirred and adsorbed at -0.08~-0.12MPa for 30-40min. The mixture is then dried until the ethanol evaporates to obtain the composite carbon-based material.
3. The carbon-based material-enhanced agricultural waste fermentation fertilizer for promoting growth and resisting stress as described in claim 2, characterized in that, In step A1, the mass ratio of the pyrolytic carbon-based material to the nitric acid solution is 1:(40-45).
4. The carbon-based material-enhanced agricultural waste fermentation fertilizer for promoting growth and resisting stress as described in claim 2, characterized in that, In step A2, the mass ratio of the chelated trace elements to the activated carbon-based material is (80-100):
1.
5. The carbon-based material-enhanced agricultural waste fermentation fertilizer for promoting growth and resisting stress as described in claim 2, characterized in that, In step A3, the mass ratio of the organic carbon source, ethanol and modified carbon-based material is (0.1-0.15):(80-100):
1.
6. The carbon-based material-enhanced agricultural waste fermentation fertilizer for promoting growth and resisting stress as described in claim 1, characterized in that, The fermentation broth is specifically prepared by: inoculating the compound bacterial agent into the culture medium at an inoculation amount of 2-5%, culturing at 30-32℃ and 180-200rpm for 3-5 days, and collecting the fermentation product; diluting the fermentation product with deionized water to obtain the fermentation broth; the mass ratio of the fermentation product to deionized water is 1:(2-3).
7. The carbon-based material-enhanced agricultural waste fermentation fertilizer for promoting growth and resisting stress according to claim 6, characterized in that, The culture medium formula is as follows: glucose 15-20 g / L, corn starch 10-15 g / L, peptone 5-10 g / L, yeast extract 5-10 g / L, amino acids 8-10 g / L, magnesium sulfate 0.4-0.5 g / L, potassium dihydrogen phosphate 0.4-0.5 g / L, and the pH value of the culture medium is 7.0-7.
2.
8. The carbon-based material-enhanced agricultural waste fermentation fertilizer for promoting growth and resisting stress according to claim 6, characterized in that, The compound bacterial agent is obtained by mixing Bacillus subtilis, Bacillus megaterium and Pseudomonas fluorescens in a live bacteria ratio of 1:1:(1-1.2).
9. The carbon-based material-enhanced agricultural waste fermentation fertilizer for promoting growth and resisting stress according to claim 1, characterized in that, The biomass material is a mixture of poultry and livestock manure, corn straw powder, and rice straw powder in a mass ratio of 1:1:(0.5-0.7); the inorganic fertilizer is a mixture of potassium dihydrogen phosphate, ammonium sulfate, and monoammonium phosphate in a mass ratio of (2-4):(1-3):(3-5).
10. A carbon-based material-enhanced agricultural waste fermentation fertilizer for promoting growth and resisting stress, as described in claim 1, characterized in that... The preparation steps for the growth-promoting and stress-resistant fertilizer are as follows: Biomass, composite carbon-based materials, carboxymethyl cellulose, and calcium chloride are premixed in a mixer for 10-15 minutes. The speed is set to 20-30 rpm, the vacuum degree is ≤-0.08 MPa, and the ambient humidity is ≤40%. Then, inorganic fertilizer is added and mixing continues for 5-10 minutes. Finally, fermentation liquid is added and mixing continues for 10-15 minutes to obtain a growth-promoting and stress-resistant fertilizer.